Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12886-018-0874-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of ocular trauma score for open globe injuries associated with metallic intraocular foreign bodies

Abstract: BackgroundThe prognostic value of the ocular trauma score (OTS) in patients who underwent 23-gauge pars plana vitrectomy (23-G PPV) for surgical removal of posterior segment metallic intaocular foreign bodies (IOFB) was evaluated.MethodsPatients who underwent 23-G PPV for surgical removal of retained metallic IOFBs were retrospectively analyzed. OTS score for each patient was calculated and raw scores were converted to their corresponding OTS categories. The final VAs in study patients were compared with their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…It is reported that the injuries usually occur at workstations, meanwhile the case with 26,5% of the injuries presented in our series. IOFB has been found to be multiple in 25% of the cases in the literature [7] and 5,9% in our series.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…It is reported that the injuries usually occur at workstations, meanwhile the case with 26,5% of the injuries presented in our series. IOFB has been found to be multiple in 25% of the cases in the literature [7] and 5,9% in our series.…”
Section: Resultssupporting
confidence: 52%
“…Previous study reported that final visual acuities of 20/40 of more were obtained in 71% of IOFB-associated open globe injuries [6]. Another study reported that functional outcomes is not more common in eyes with IOFB [7]. Study from Kuhn et al reported that variable of IOFB was not included in OTS prognostic parameter [1].…”
Section: Resultsmentioning
confidence: 99%
“…IOFBs occurrence in this population has been consistent over time. Previous reports investigating the characteristics and prognostic factors of IOFBs were largely retrospective [1, 79]. Our study suffers from the same limitation.…”
Section: Discussionmentioning
confidence: 90%
“…Some studies have verified the reliability and predictability of this assessment system [12]. Several studies have reported that the OTS can be utilized to accurately predict outcomes [22,31,32]. However, Oiticica et al [33] found that the OTS had limited value in predicting long-term VA in children.…”
Section: Discussionmentioning
confidence: 95%